2018
DOI: 10.1094/phyto-10-17-0339-r
|View full text |Cite
|
Sign up to set email alerts
|

Movement and Motion of Soybean Cyst Nematode Heterodera glycines Populations and Individuals in Response to Abamectin

Abstract: Two new in vitro methods were developed to analyze plant-parasitic nematode behavior, at the population and the individual organism levels, through time-lapse image analysis. The first method employed a high-resolution flatbed scanner to monitor the movement of a population of nematodes over a 24-h period at 25°C. The second method tracked multiple motion parameters of individual nematodes on a microscopic scale, using a high-speed camera. Changes in movement and motion of second-stage juveniles (J2) of the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Significant effects were observed on J2 movement and penetration at several soil depths. In previous experiments, we found that H. glycines was sensitive to abamectin at concentrations of 1-10 mg/ml (Jensen et al 2018). A similar concentration of 1.56 mg/ml was reported to paralyze M. incognita (Faske and Starr 2006).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Significant effects were observed on J2 movement and penetration at several soil depths. In previous experiments, we found that H. glycines was sensitive to abamectin at concentrations of 1-10 mg/ml (Jensen et al 2018). A similar concentration of 1.56 mg/ml was reported to paralyze M. incognita (Faske and Starr 2006).…”
Section: Discussionmentioning
confidence: 59%
“…Nematodes incubated in leachates of soil planted with treated seeds and in control solutions were analyzed using motion analysis of individual nematodes described by Jensen et al (2018). J2s in 30 ml of suspension from the treatments described above were placed on a microscope slide with coverslip and observed with overhead light microscopy (Leica LED 5000 light attached to Leica M205 C stereoscope) at 63× magnification (6.3× magnification, 10× eyepiece, and 1× camera).…”
Section: Methodsmentioning
confidence: 99%
“…An example of open source hardware and software for the automated counting of bacterial colonies showed that high-resolution images from flatbed scanners (1200 dpi and higher) were superior than those from digital cameras for bacterial enumeration [16]. Besides applications in microbiology, our bacterial enumeration system can be diversified for imaging, counting, and tracking other microorganisms on agar plates, such as C. elegans and parasitic nematodes [17][18][19][20]. For this purpose, a number of open source image processing and analysis techniques are freely available through the ImageJ software and the scientific imaging community [14,21,22].…”
Section: Limitations and Future Scopementioning
confidence: 99%
“…Significant effects were observed on J2 movement and penetration at several soil depths. In previous experiments, we found that H. glycines was sensitive to abamectin at concentrations of 1 to 10 μg/ml (Jensen et al 2017). A similar concentration of 1.56 μg/ml was reported to paralyze M.…”
Section: Discussionmentioning
confidence: 61%
“…Nematodes incubated in leachates of soil planted with treated seeds and in control solutions were analyzed using motion analysis of individual nematodes described by Jensen et al 2017. J2s in 30 ml of suspension from the treatments described above were placed on a microscope slide with coverslip and observed with overhead light microscopy (Leica LED 5000 light attached to Leica M205 C stereoscope) at 63x magnification (6.3x magnification, 10x…”
Section: Methodsmentioning
confidence: 99%